Function and Role of ATP-Binding Cassette Transporters as Receptors for 3D-Cry Toxins - Ryoichi Sato; Satomi Adegawa; Xiaoyi Li; Shiho Tanaka; Haruka Endo (Toxins, 2019)
When ABC transporter family C2 (ABCC2) and ABC transporter family B1 (ABCB1) were heterologously expressed in non-susceptible cultured cells, the cells swelled in response to Cry1A and Cry3 toxins, respectively. Consistent with the notion that 3D-Cry toxins form cation-permeable pores, Bombyx mori ABCC2 (BmABCC2) facilitated cation-permeable pore formation by Cry1A when expressed in Xenopus oocytes. Furthermore, BmABCC2 had a high binding affinity (KD) to Cry1Aa of 3.1 × 10−10 M. These findings suggest that ABC transporters, including ABCC2 and ABCB1, are functional receptors for 3D-Cry toxins. In addition, the Cry2 toxins most distant from Cry1A toxins on the phylogenetic tree used ABC transporter A2 as a receptor. These data suggest that 3D-Cry toxins use ABC transporters as receptors. In terms of inducing cell swelling, ABCC2 has greater activity than cadherin-like receptor. The pore opening of ABC transporters was hypothesized to be linked to their receptor function, but this was repudiated by experiments using mutants deficient in export activity. The synergistic relationship between ABCC2 and cadherin-like receptor explains their ability to cause resistance in one species of insect.